Current Concepts in Sudden Cardiac Death in Adults (Revista de Medicina Clinica, 2017)
Sudden cardiac death (SCD) is one of the biggest challenges not only of modern cardiology, but also of modernsociety and can be considered along with infant mortality an indicator of general population health, this article itemphasizes on the causes of sudden cardiac death including new diseases that 10 years ago were not yet known andtherefore are subdiagnosticated and underrated; besides generalities quickly review the symptoms and the most currenttreatment in MSC.Rev Med Clin 2017;1(1)30-39.
Keywords: suddent cardiac death; hearth; adult; cardiovascular diseases